Distribuição vertical de fósforo em sedimentos do Igarapé Tucunduba e Rio Guamá - SILVA, David Antonio de Lima (2018)
Phosphorus is an important macronutrient. Its availability in the aquatic environment occurs through the weathering of rocks mainly in the form of apatite and anthropic action, through the disposal of effluents and fertilizers in the environment. High concentrations of phosphorus may indicate a possible eutrophication process of the aquatic system. This study had as objective to evaluate the possible sources and vertical distribution of total phosphorus, as well as the sediment granulometry of the mouth of the Tucunduba stream and the left bank of the Guamá river. Water samples were collected for the determination of the hydrochemical parameters as: temperature, pH, conductivity and total dissolved solids, through a multiparameter analyzer. For the extraction of the P-total, the SEDEX method was used and for the analysis the spectrometric technique of the molybdate blue was emitted, because the extracted sedimentary phosphorus forms are like orthophosphates. The highest concentration of total phosphorus in the first 5 cm of sediments of the Tucunduba Igarapé was obtained, since this ecosystem presents great anthropic influence through the emission of effluents in its waters. In the sediments of the Guamá River, lower concentrations of total phosphorus were observed in the surface layer in relation to the sediments of the Tucunduba stream, due to the greater distance between this point and the drainage channels of the city of Belém. The granulometric analysis indicated a high Hydrodynamics, but the fraction of lamoso sediments was predominant.